2021
DOI: 10.1038/s41598-021-91125-2
|View full text |Cite
|
Sign up to set email alerts
|

Circulation derived from 4D flow MRI correlates with right ventricular dysfunction in patients with tetralogy of Fallot

Abstract: We used 4D-flow MRI to investigate circulation, an area integral of vorticity, in the main pulmonary artery (MPA) as a new hemodynamic parameter for assessing patients with a repaired Tetralogy of Fallot (TOF). We evaluated the relationship between circulation, right ventricular (RV) function and the pulmonary regurgitant fraction (PRF). Twenty patients with a repaired TOF underwent cardiac MRI. Flow-sensitive 3D-gradient sequences were used to obtain 4D-flow images. Vortex formation in the MPA was visualized,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Previous studies have shown the utility of 4D flow-derived vorticity metrics which has been associated with inefficient blood flow in patients with pulmonary [ 12 , 14 , 15 , 20 23 ] and aortic disease [ 13 , 16 ]. Although qualitative vortices and swirling has been associated with diseased states [ 13 , 22 ], our study shows global quantitative metrics of vorticity increasing post-PEA in patients with CTEPH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown the utility of 4D flow-derived vorticity metrics which has been associated with inefficient blood flow in patients with pulmonary [ 12 , 14 , 15 , 20 23 ] and aortic disease [ 13 , 16 ]. Although qualitative vortices and swirling has been associated with diseased states [ 13 , 22 ], our study shows global quantitative metrics of vorticity increasing post-PEA in patients with CTEPH.…”
Section: Discussionmentioning
confidence: 99%
“…Other methods focus on the balance between clockwise and counterclockwise helicity and normalized helicity intensity in aortic valvular disease [18,19]. 4D flow CMR in the PAs has shown promise for characterizing RV-PA dynamics in healthy subjects and patients with PH through fluid dynamics derived metrics of secondary flow profiles, such as vorticity and helicity, specifically in severe stages of PH and large dilatation of the pulmonary trunk [12,14,[20][21][22][23]. However, comprehensive analyses of velocity flow profiles and secondary flow profiles including vorticity and helicity have yet to be investigated in patients with CTEPH following a PEA to determine their utility in evaluating recovery and reverse remodeling of the RV.…”
Section: Introductionmentioning
confidence: 99%
“…In our study cohort, MPA diameter in patients with RV moderate-severe dilatation was larger than that in patients with RV mild dilatation. Other studies paid more attention to hemodynamic factors in pulmonary artery, with some suggesting that increased longitudinal circulation of MPA was associated with RV dysfunction (35). In addition, it has been shown that end-diastolic anterior blood ow in the MPA is associated with poor outcomes in patients with rTOF(36).…”
Section: Preoperative Clinical Featuresmentioning
confidence: 99%
“…[ 13 ] Tetralogy of Fallot (TOF) is the most common cyanotic heart condition in children that have survived beyond the neonatal period. [ 14 ] As described by Joseph et al, [ 15 ] they generated induced pluripotent stem cell (iPSC) lines from 5 patients with single ventricle disease (SVD), 5 patients with TOF, and 5 healthy individuals (non-CHD). Then, they differentiated all iPSC lines into cardiomyocytes (iPSC-CMs) and used highly enriched iPSC-CMs for RNA sequencing.…”
Section: Introductionmentioning
confidence: 99%